Styrene-acrylate toner composition

JP2022119721A5Active Publication Date: 2025-01-21XEROX CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022004313
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-04
Filing Date
2022-01-14
Publication Date
2025-01-21
Estimated Expiration
2042-01-14

AI Technical Summary

Technical Problem

Current toner compositions, particularly styrene-acrylate toners, fail to meet the requirements of high temperature offset, gloss, aging, and storage stability, especially in single component development machines.

Method used

A toner particle comprising a core and a shell, where the core consists of multiple styrene-acrylate copolymers with specific molecular weights and glass transition temperatures, and the shell is made from styrene-acrylate copolymers, prepared through an emulsion aggregation process involving the formation of a latex, aggregation, and coalescence, with the use of flocculating and chelating agents to control properties.

Benefits of technology

The solution enhances toner performance by improving high temperature offset, gloss, and storage stability, achieving desired properties for single component development machines.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a toner that meets requirements of an intended machine including hot offset, gloss, aging, and storage stability characteristics.SOLUTION: A toner comprises: toner particles each including a core and a shell thereover, where the core comprises at least one styrene-acrylate copolymer selected from styrene-acrylate copolymer 1, styrene-acrylate copolymer 2, and styrene-acrylate copolymer 3, and combinations thereof; a wax; and an optional colorant. The shell comprises at least one styrene-acrylate copolymer selected from styrene-acrylate copolymer 1, styrene acrylate copolymer 2, styrene acrylate copolymer 3, and combinations thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] A toner comprising toner particles including a core and a shell thereon, wherein the core comprises at least one styrene-acrylate copolymer selected from a first core styrene-acrylate copolymer, a second core styrene-acrylate copolymer, and a third core styrene-acrylate copolymer, or a combination thereof, a wax, and an optional colorant, wherein the first core styrene-acrylate copolymer has a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an initial glass transition temperature of about 57.0 °C to about 61.0 °C, the second core styrene-acrylate copolymer has a weight average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an initial glass transition temperature of about 53.0 °C to about 57.0 °C, the third core styrene-acrylate copolymer has a weight average molecular weight of about 33,000 g / mol to about 39,000 g / mol and an initial glass transition temperature of about 49.0 °C to about 53.0 °C, the shell comprises at least one styrene-acrylate copolymer selected from a first shell styrene-acrylate copolymer, a second shell styrene-acrylate copolymer, a third shell styrene-acrylate copolymer, or a combination thereof, the first shell styrene-acrylate copolymer has a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an initial glass transition temperature of about 57.0 °C to about 61.0 °C, the second shell styrene-acrylate copolymer has a weight average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an initial glass transition temperature of about 53.0 °C to about 57.0 °C, the third shell styrene-acrylate copolymer has a weight average molecular weight of about 33,000 g / mol to about 39,000 g / mol and an initial glass transition temperature of about 49.0 °C to about 53.0 °C, is disclosed.

[0002] A method for preparing a toner comprising emulsion aggregated core-shell toner particles, comprising a core and a shell thereon, wherein the core comprises at least one styrene-acrylate copolymer selected from a first styrene-acrylate copolymer, a second styrene-acrylate copolymer, and a third styrene-acrylate copolymer, or a combination thereof, a wax, and an optional colorant, wherein the first styrene-acrylate copolymer is approximately 32,000 g / mol to approximately The first styrene-acrylate copolymer has a weight-average molecular weight of 38,000 g / mol and an initial glass transition temperature of approximately 57.0°C to approximately 61.0°C, the second styrene-acrylate copolymer has a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol and an initial glass transition temperature of approximately 53.0°C to approximately 57.0°C, the third styrene-acrylate copolymer has a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol and an initial glass transition temperature of approximately 49.0°C to approximately 53.0°C, and the shell is made of the first styrene Further disclosed is a method comprising at least one styrene-acrylate copolymer selected from -acrylate copolymer, second styrene-acrylate copolymer, third styrene-acrylate copolymer, or a combination thereof, the method comprising: obtaining a core styrene-acrylate copolymer latex, an optionally aqueous dispersion of a colorant, and an aqueous dispersion of wax; forming a mixture of the core styrene-acrylate copolymer latex, an optionally aqueous dispersion of a colorant, and an aqueous dispersion of wax; heating the mixture to a first temperature; maintaining the first temperature to form agglomerated toner particles; adding a shell styrene-acrylate copolymer latex to form a shell on the agglomerated particles; optionally adding a chelating agent solution; stopping further agglomeration and raising the temperature to a second temperature higher than the first temperature to coalesce the agglomerated particles; and subsequently cooling, optionally washing, and recovering the emulsion agglomerated toner particles.

[0003] Styrene-acrylate toner compositions are desirable for toners and toner / developers. The toners preferably meet several requirements of the intended machine, including high-temperature offset, gloss, aging, and storage stability properties.

[0004] U.S. Patent No. 7,455,943, which is incorporated herein by reference in its entirety, describes a toner comprising emulsion-aggregated toner particles of a binder containing a non-crosslinked styrene acrylate polymer, at least one colorant, at least one wax, and aluminized silica, wherein the amount of aluminum metal in the toner particles is about 50 ppm to about 600 ppm. Such a toner may provide a high level of gloss while maintaining a low minimum fixed temperature. The aluminized silica acts as a coagulant during the emulsion aggregation process of the toner.

[0005] U.S. Patent No. 10,409,185, which is incorporated herein by reference in its entirety, describes a method for forming a toner. In embodiments, such a method is to form a toner from a mixture of at least one resin, at least one wax, and optionally at least one colorant, wherein the at least one wax is of one type and a predetermined PER of the toner. 10 Toner PER exists in the amount selected to provide a value, to form 10 The measurement of the toner's measured PER 10 The value is a predetermined PER 10 This includes measuring a value that is less than or equal to a certain value. Toner formed using this method is also provided.

[0006] U.S. Patent Application No. 16 / 800,176, filed on 25 February 2020 and titled “Dual Wax Toner Composition,” which is incorporated herein by reference in its entirety, describes a toner composition comprising a first wax and a second wax distinct from the first wax, wherein the first wax comprises paraffin wax and the second wax comprises polymethylene wax, and further comprises at least one polyester and an optional colorant.

[0007] Currently available toner compositions are suitable for their intended purposes. However, improved toner compositions are still needed. Furthermore, improved styrene-acrylate toner compositions are still needed. Moreover, in embodiments, for single-component developing machines using black toner, improved styrene-acrylate toner compositions suitable for single-component developing machines are still needed. Moreover, improved styrene-acrylate toner compositions that meet the requirements of the intended machine, including hot offset, gloss, aging, and storage stability properties, are still needed.

[0008] Appropriate components and processes of the aforementioned U.S. patents and patent application publications may be selected for this disclosure in their respective embodiments. Furthermore, various publications, patents, and published patent applications are referenced by specific citations throughout this application. The disclosures of publications, patents, and published patent applications referenced in this application are incorporated by reference to more fully illustrate the current technology to which the present invention relates. [Overview of the project]

[0009] Toner comprising toner particles including a core and a shell thereon, wherein the core comprises at least one styrene-acrylate copolymer selected from a first core styrene-acrylate copolymer, a second core styrene-acrylate copolymer, and a third core styrene-acrylate copolymer, or a combination thereof, and a wax and an optional colorant, wherein the first core styrene-acrylate copolymer comprises about 32, The first core styrene-acrylate copolymer has a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol and an onset glass transition temperature of approximately 57.0°C to approximately 61.0°C, while the second core styrene-acrylate copolymer has a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol and an onset glass transition temperature of approximately 53.0°C to approximately 57.0°C, while the third core styrene-acrylate copolymer has a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol and approximately 49 The material has an onset glass transition temperature of 0°C to approximately 53.0°C, and the shell comprises at least one styrene-acrylate copolymer selected from a first shell styrene-acrylate copolymer, a second shell styrene-acrylate copolymer, a third shell styrene-acrylate copolymer, or a combination thereof, wherein the first shell styrene-acrylate copolymer has a weight-average molecular weight of approximately 32,000 g / mol to approximately 38,000 g / mol, and approximately 57. A toner is described in which a second shell styrene-acrylate copolymer has a starting glass transition temperature of 0°C to approximately 61.0°C, a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol, and a starting glass transition temperature of approximately 53.0°C to approximately 57.0°C, and a third shell styrene-acrylate copolymer has a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol, and a starting glass transition temperature of approximately 49.0°C to approximately 53.0°C.

[0010] A method for preparing a toner comprising emulsion aggregated core-shell toner particles, comprising a core and a shell thereon, wherein the core comprises at least one styrene-acrylate copolymer selected from a first styrene-acrylate copolymer, a second styrene-acrylate copolymer, and a third styrene-acrylate copolymer, or a combination thereof, a wax, and an optional colorant, wherein the first styrene-acrylate copolymer is present in a concentration of approximately 32,000 g / mol. The first styrene-acrylate copolymer has a weight-average molecular weight of approximately 38,000 g / mol and an initial glass transition temperature of approximately 57.0°C to approximately 61.0°C, the second styrene-acrylate copolymer has a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol and an initial glass transition temperature of approximately 53.0°C to approximately 57.0°C, the third styrene-acrylate copolymer has a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol and an initial glass transition temperature of approximately 49.0°C to approximately 53.0°C, and the shell is made of the first styrene The present invention also describes a method comprising at least one styrene-acrylate copolymer selected from n-acrylate copolymer, a second styrene-acrylate copolymer, a third styrene-acrylate copolymer, or a combination thereof, the method comprising: obtaining a core styrene-acrylate copolymer latex, an optionally aqueous dispersion of a colorant, and an aqueous dispersion of wax; forming a mixture of the core styrene-acrylate copolymer latex, an optionally aqueous dispersion of a colorant, and an aqueous dispersion of wax; heating the mixture to a first temperature; maintaining the first temperature to form agglomerated toner particles; adding a shell styrene-acrylate copolymer latex to form a shell on the agglomerated particles; optionally adding a chelating agent solution; stopping further agglomeration and raising the temperature to a second temperature higher than the first temperature to coalesce the agglomerated particles; and subsequently cooling, optionally washing, and recovering the emulsion agglomerated toner particles. [Modes for carrying out the invention]

[0011] The toner particles described consist of a core resin containing a styrene-acrylate copolymer, a shell resin containing a styrene-acrylate copolymer, an optional pigment, and a wax-release agent, and in embodiments, are prepared using a flocculant and a chelating agent.

[0012] In embodiments, a toner is described, which is a toner particle comprising a core and a shell thereon, wherein the core comprises at least one styrene-acrylate copolymer, in embodiments comprising a combination of at least two styrene-acrylate copolymers selected from a first styrene-acrylate copolymer (styrene-acrylate copolymer 1), a second styrene-acrylate copolymer (styrene-acrylate copolymer 2), and a third styrene-acrylate copolymer (styrene-acrylate copolymer 3). The material comprises toner particles, wax, and an optional colorant, wherein the first core styrene-acrylate copolymer has a weight-average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an onset glass transition temperature of about 57.0°C to about 61.0°C, the second core styrene-acrylate copolymer has a weight-average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an onset glass transition temperature of about 53.0°C to about 57.0°C, and the third core styrene-acrylate copolymer has a weight-average molecular weight of about 33,000 g / mol to about 39, The shell has a weight-average molecular weight of 000 g / mol and an onset glass transition temperature of approximately 49.0°C to approximately 53.0°C, and comprises at least one styrene-acrylate copolymer selected from a first shell styrene-acrylate copolymer, a second shell styrene-acrylate copolymer, a third styrene-acrylate copolymer, or a combination thereof, wherein the first shell styrene-acrylate copolymer (styrene-acrylate copolymer 1) has a weight-average molecular weight of approximately 32,000 g / mol to approximately 38,000 g / mol, and The second shell styrene-acrylate copolymer (styrene-acrylate copolymer 2) has a starting glass transition temperature of approximately 57.0°C to approximately 61.0°C, a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol, and a starting glass transition temperature of approximately 53.0°C to approximately 57.0°C, while the third shell styrene-acrylate copolymer (styrene-acrylate copolymer 3) has a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol, and a starting glass transition temperature of approximately 49.0°C to approximately 53.0°C.

[0013] The molecular weight is determined by gel permeation chromatography according to standard methods. The onset Tg (onset glass transition temperature) is measured using differential scanning calorimetry and is defined as the intersection of lines tangent to both the heat flow curves before and after the glass transition.

[0014] In embodiments, a toner is described, which is an emulsion-aggregated toner particle comprising a core and a shell thereon, wherein the core comprises an emulsion-aggregated toner particle comprising a combination of at least two styrene-acrylate copolymers selected from a first core styrene-acrylate copolymer, a second styrene-acrylate copolymer, and a third styrene-acrylate copolymer, a wax, and an optional colorant, wherein the first core styrene-acrylate copolymer has a weight-average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an on-start glass transition temperature of about 57.0°C to about 61.0°C, and the second core styrene-acrylate copolymer has a weight-average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an on-start glass transition temperature of about 53.0°C to about 57.0°C The third core styrene-acrylate copolymer has an initial glass transition temperature, a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol, and an initial glass transition temperature of approximately 49.0°C to approximately 53.0°C. The shell comprises at least one styrene-acrylate copolymer selected from the first shell styrene-acrylate copolymer, the second shell styrene-acrylate copolymer, the third, or a combination thereof. The first shell styrene-acrylate copolymer has a weight-average molecular weight of approximately 32,000 g / mol to approximately 38,000 g / mol, and an initial glass transition temperature of approximately 57.0°C to approximately 61.0°C. The second shell styrene-acrylate copolymer has a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol, and an initial glass transition temperature of approximately 53.0°C to approximately 57.Having a starting glass transition temperature of 0°C, the toner contains approximately 50–80 weight percent core, or approximately 50–60 weight percent core, or approximately 52–56 weight percent core, approximately 20–36 weight percent shell, or approximately 24–32 weight percent shell, or approximately 26–30 weight percent shell, approximately 3–10 weight percent colorant, or approximately 4–8 weight, or approximately 5–7 weight percent colorant, approximately 5–20 weight percent wax, or approximately 7–20 weight percent wax, or approximately 9–16 weight percent wax, where percentages are weight percentages based on the total weight of the toner.

[0015] In certain embodiments, the toner core comprises a combination of a first styrene-acrylate copolymer having a weight-average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an on-start glass transition temperature of about 57.0°C to about 61.0°C, and a second core styrene-acrylate copolymer having a weight-average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an on-start glass transition temperature of about 53.0°C to about 57.0°C, and the toner shell comprises a single shell resin, the shell resin being the first core styrene-acrylate copolymer having a weight-average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an on-start glass transition temperature of about 57.0°C to about 61.0°C.

[0016] In certain embodiments, a toner is described, which comprises a pigment, which in embodiments is carbon black, present in an amount of about 3 to about 10 weight percent, or about 4 to about 8 weight percent, or about 5 to about 7 weight percent, based on the total weight of the toner particles; a wax, which in embodiments is polyethylene wax, paraffin wax, or a combination thereof, present in an amount of 7 to about 20 weight percent, or about 9 to about 16 weight percent, based on the total weight of the toner particles; and a core resin comprising at least one styrene-acrylate copolymer, which in embodiments comprises at least two styrene copolymers selected from the group consisting of styrene-acrylate copolymer 1, styrene-acrylate copolymer 2, and styrene-acrylate copolymer 3. The material comprises a core resin containing a combination of styrene-acrylate copolymers, present in an amount of about 50 to about 60 weight percent, or about 52 to about 56 weight percent, based on the total weight of the toner particles; a shell resin containing at least one styrene-acrylate copolymer selected from the group consisting of styrene-acrylate copolymer 1, styrene-acrylate copolymer 2, styrene-acrylate copolymer 3, and combinations thereof, present in an amount of about 26 to about 30 weight percent, or about 26 to about 28 weight percent, based on the total weight of the toner particles; a flocculant, which in embodiments is polyaluminum chloride, present in an amount of about 0.18 pph (percentage) (based on the total weight of the toner); and a chelating agent, which in embodiments is ethylene diamine tetraacetic acid (EDTA), present in an amount of about 0.79 pph (percentage) (based on the total weight of the toner). In this specification, pph is intended to be described based on the raw materials actually remaining in the final toner.

[0017] Core resin.

[0018] The toner cores described herein comprise one or a combination of styrene-acrylate copolymers. In embodiments, the core resin comprises a first styrene-acrylate copolymer, a second styrene-acrylate copolymer, and optionally a third styrene-acrylate copolymer. The first, second, and third styrene-acrylate copolymers are distinct. In embodiments, the shell resin comprises at least one styrene-acrylate copolymer, in embodiments, a combination of two styrene-acrylate copolymers, and in further embodiments, a combination of three styrene-acrylate copolymers. Each styrene-acrylate copolymer has a specific molecular weight and glass transition temperature. The styrene-acrylate copolymers are selected to provide a specific molecular weight to the toner as a whole. Thus, unique combinations of core latex that provide desired properties to the toner as a whole, such as toner molecular weight, glass transition temperature, melt viscosity, and triboelectric properties, are described.

[0019] In this embodiment, the toner is prepared using a coagulant, a chelating agent, or both a coagulant and a chelating agent.

[0020] In the embodiment, the amount of coagulant added when preparing the toner is about 0.01 to about 1.00, or about 0.05 to about 0.50, or about 0.10 to about 0.20 parts per pound (pph), based on the total weight of the dry toner particles.

[0021] In the embodiment, the amount of chelating agent added when preparing the toner is about 0.01 to about 1.50, or about 0.50 to about 1.00, or about 0.75 to about 0.85 parts per pound (pph), based on the total weight of the dry toner particles.

[0022] In the embodiment, the amount of flocculant added when preparing the toner is selected to provide a residual amount of flocculant in the final toner of about 1 to about 1,000, or about 350 to about 550, or about 425 to about 475 parts per million (ppm), based on the total weight of the toner. In the case of aluminum-based flocculants, the active ingredient in the flocculant is elemental aluminum ions. Inert counterions of the flocculant are filtered out. In the case of aluminum-based flocculants, verification of residual flocculant in the toner can be done by testing for elemental aluminum. Therefore, in the embodiment, the toner is selected to provide a residual amount of aluminum in the final toner of about 1 to about 1,000, or about 350 to about 550, or about 425 to about 475 parts per million (ppm), based on the total weight of the dry toner particles.

[0023] In the embodiment, the amount of chelating agent added when preparing the toner is selected to provide a residual amount of chelating agent in the final toner of about 0 to about 8,000, or about 10 to about 100, or about 20 to about 50 parts per million (ppm), based on the total weight of the dry toner particles.

[0024] The desired rheological properties of the final toner can be achieved by selecting a flocculant, a chelating agent, or a combination thereof. For example, the melt viscosity, as measured by the melt flow index (MFI), can be decreased by using a larger amount of chelating agent or increased by using a larger amount of flocculant. Also, the Tg can be decreased by using a larger amount of chelating agent.

[0025] In embodiments, toner particles include various combinations of the three styrene-acrylate latex:styrene-acrylate copolymer 1, styrene-acrylate copolymer 2, and styrene-acrylate copolymer 3 described herein, and are prepared using various combinations.

[0026] In an embodiment, styrene-acrylate copolymer 1 is a styrene-acrylate copolymer in which the molar ratio of the monomers is about 80 to about 90 parts of styrene, about 10 to about 20 parts of n-butyl acrylate, and about 0.5 to about 3 parts of β-carboxyethyl acrylate, the weight average molecular weight (Mw) value is about 32,000 g / mol to about 38,000 g / mol, and the number average molecular weight (Mn) value is about 13,000 g / mol to about 18,000 g / mol. Both Mw and Mn can be determined using gel permeation chromatography (GPC). In an embodiment, styrene-acrylate copolymer 1 has a glass transition temperature (Tg) within the range of about 55°C to about 65°C, about 57°C to about 64°C, or about 57°C to about 61°C. Tg can be determined using differential scanning calorimetry (DSC). The onset Tg is defined as the intersection of the lines tangent to the heat flow curves both before and after the glass transition.

[0027] In an embodiment, styrene-acrylate copolymer 2 is a styrene-acrylate copolymer in which the molar ratio of the monomers is about 70 to about 80 parts of styrene, about 20 to about 30 parts of n-butyl acrylate, and about 0.5 to about 3.0 parts of β-carboxyethyl acrylate, the weight average molecular weight (Mw) value is about 52,000 g / mol to about 58,000 g / mol, and the number average molecular weight (Mn) value is about 28,000 g / mol to about 33,000 g / mol. Both Mw and Mn can be determined using gel permeation chromatography (GPC). In an embodiment, styrene-acrylate copolymer 2 has a glass transition temperature (Tg) within the range of about 50.0°C to about 60.0°C, about 52.0°C to about 59.9°C, or about 53.0°C to about 57.0°C. Tg can be determined using differential scanning calorimetry (DSC).

[0028] In an embodiment, the styrene-acrylate copolymer 3 is a styrene-acrylate copolymer in which the molar ratio of monomers is about 70 to about 80 parts of styrene, about 20 to about 30 parts of n-butyl acrylate, and about 0.5 to about 3.0 parts of β-carboxyethyl acrylate, the weight average molecular weight (Mw) value is about 33,000 g / mol to about 39,000 g / mol, and the number average molecular weight (Mn) value is about 13,000 g / mol to about 18,000 g / mol. Both Mw and Mn can be determined using gel permeation chromatography (GPC). In an embodiment, the styrene-acrylate copolymer 3 has a glass transition temperature (Tg) within the range of about 46.0 °C to about 56.0 °C, about 48.0 °C to about 54.0 °C, or about 49.0 °C to about 53.0 °C. Tg can be determined using differential scanning calorimetry (DSC).

[0029] In an embodiment, the toner particle core resin and the shell resin are selected to provide the final toner with a weight average molecular weight (Mw) of about 38,000 g / mol to about 48,000 g / mol, or about 40,000 g / mol to about 46,000 g / mol, or about 42,000 g / mol to about 45,000 g / mol, and a number average molecular weight (Mn) value of about 16,000 g / mol to about 23,000 g / mol, or about 17,000 g / mol to about 22,000 g / mol, or about 18,000 g / mol to about 21,000 g / mol. The Mw and Mn of the toner can be determined using gel permeation chromatography (GPC).

[0030] In an embodiment, the toner particle core resin and the shell resin are selected to provide the final toner with an initial glass transition temperature (Tg) within the range of about 53.0 °C to about 60.0 °C, about 54.0 °C to about 58.0 °C, or about 55.0 °C to about 57.0 °C. The Tg of the toner can be determined using differential scanning calorimetry (DSC). As described above, the "initial Tg" is defined as the intersection of the lines tangent to the heat flow curves both before and after the glass transition. Unless otherwise specified, when used herein, both "Tg" and "initial Tg" refer to the initial glass transition temperature.

[0031] The molecular weight properties of the core resin polymer and shell resin polymer can be controlled using known chain transfer agents. Examples of chain transfer agents include dodecanethiol, dodecyl mercaptan, octanthiol, carbon tetrabromide, and carbon tetrachloride, and they are present in various suitable amounts, for example, about 0.1 to about 10 weight percent of the total monomer, for example, about 0.1 to about 8 weight percent, or about 0.2 to about 5 weight percent of the total monomer.

[0032] In some embodiments, the toner particles have a core-shell structure. The core comprises a combination of styrene-acrylate copolymers. In some embodiments, the core comprises a combination of a first styrene-acrylate copolymer, a second styrene-acrylate copolymer, and optionally a third styrene-acrylate copolymer, where the first core styrene-acrylate copolymer is styrene-acrylate copolymer 1, the second core styrene-acrylate copolymer is styrene-acrylate copolymer 2, and the optionally third styrene-acrylate copolymer is styrene-acrylate copolymer 3. In other embodiments, the core comprises at least one of styrene-acrylate copolymer 1, styrene-acrylate copolymer 3, or a combination of styrene-acrylate copolymer 1 and styrene-acrylate copolymer 3. In other embodiments, the core comprises at least one of styrene-acrylate copolymer 2, styrene-acrylate copolymer 3, or a combination of styrene-acrylate copolymer 3. In certain embodiments, the core includes a combination of a first styrene-acrylate copolymer and a second styrene-acrylate copolymer.

[0033] The shell comprises at least one styrene-acrylate copolymer selected from styrene-acrylate 1, styrene-acrylate 2, and styrene-acrylate 3, or a combination thereof. In embodiments, the shell comprises a first styrene-acrylate copolymer and a second styrene-acrylate copolymer, where the first shell styrene-acrylate copolymer is styrene-acrylate copolymer 1 and the second shell styrene-acrylate copolymer is styrene-acrylate copolymer 2. In certain embodiments, the shell comprises only styrene-acrylate copolymer 1.

[0034] Therefore, in this embodiment, the toner particles have a core-shell structure, the core comprises a first, second, and optionally third styrene-acrylate copolymer, the first core styrene-acrylate copolymer being styrene-acrylate copolymer 1, the second core styrene-acrylate copolymer being styrene-acrylate copolymer 2, and the optionally third styrene-acrylate copolymer being styrene-acrylate copolymer 3; and the shell comprises the first and second styrene-acrylate copolymers, the first shell styrene-acrylate copolymer being styrene-acrylate copolymer 1, and the second shell styrene-acrylate copolymer being styrene-acrylate copolymer 2. Furthermore, in this embodiment, the core may contain a colorant comprising a combination of carbon black and cyan pigment.

[0035] In other embodiments, the toner particles have a core-shell structure, where the core comprises one or a combination of styrene-acrylate copolymer 1 and styrene-acrylate copolymer 3, and the shell comprises one or a combination of styrene-acrylate copolymer 1, styrene-acrylate copolymer 2, and styrene-acrylate copolymer 3. In one embodiment, the core comprises styrene-acrylate copolymers 1 and 3, and the shell comprises a single styrene-acrylate copolymer 1. In another embodiment, the core comprises styrene-acrylate copolymers 1 and 3, and the shell is styrene-acrylate copolymer 2. In yet another embodiment, the core comprises styrene-acrylate copolymers 2 and 3, and the shell is styrene-acrylate copolymer 2. In yet another embodiment, the core comprises styrene-acrylate copolymer 3, and the shell comprises styrene-acrylate copolymer 1. In yet another embodiment, the core comprises styrene-acrylate copolymer 3, and the shell comprises styrene-acrylate copolymer 2. In another embodiment, the core comprises styrene-acrylate copolymer 3, and the shell comprises styrene-acrylate copolymer 3. In a particular embodiment, the toner particle has a core-shell structure, where the core comprises a combination of styrene-acrylate copolymer 1 and styrene-acrylate copolymer 2, and the shell comprises styrene-acrylate copolymer 1 alone. Furthermore, in embodiments, the core may be a colorant comprising at least one of black, carbon black, cyan, magenta pigment, and yellow pigment, and in embodiments, copper phthalocyanine, PR122, PR269, PY74, or a combination thereof.

[0036] The toner particle core may comprise a styrene-acrylate copolymer as described herein, as well as a combination of colorants and waxes as described herein. Once the core particles are formed and aggregated to a desired diameter, a thin outer shell is then formed on the core particles. The shell may consist of one or a combination of styrene-acrylate copolymers as described herein.

[0037] Shell latex may be added to the core toner particle aggregates in any preferred or desired amount. In embodiments, shell latex may be added to the core toner particle aggregates in an amount of about 20 to about 45 weight percent of the total binder material (i.e., the total amount of core latex and shell latex), or about 25 to about 40 weight percent, or about 30 to about 235 weight percent, based on the total weight of the binder material (the sum of core latex and shell latex).

[0038] In embodiments, the toner comprises about 50 to about 60 weight percent of core resin, or about 52 to about 56 weight percent of core resin, about 26 to about 30 weight percent of shell resin, or about 26 to about 28 weight percent of shell resin, about 3 to about 10 weight percent of colorant, or about 4 to about 8 percent, or about 5 to about 7 percent of colorant, and about 7 to about 20 weight percent of wax, or about 9 to about 16 percent of wax, where the percentages are weight percentages based on the total weight of the toner.

[0039] The total amount of binder, including the core resin and shell resin, may be about 60 to about 95 percent by weight of the toner particles (i.e., toner particles excluding external additives), or about 70 to about 90 percent by weight of the toner particles.

[0040] In embodiments, polymers for the core and shell binders can each be formed into latex for use in a subsequent emulsion-aggregated toner particle formation process. Such a process may be carried out by mixing monomer components, including optional additives, in an aqueous phase in the presence of one or more surfactants, and then polymerizing the monomers using, for example, an initiator, to form small-diameter seed particles. For example, a latex can be obtained having an aqueous phase containing polymer particles with small diameters of about 5 nanometers (nm) to about 500 nm, or about 50 nm to about 300 nm. Any preferred method for forming latex from monomers can be used. The latex particle diameter is given as the volume-average median particle diameter measured using a Nanotrac particle size analyzer. "Nanotrac" is the model name of a particle size analyzer manufactured by Microtrac, which uses dynamic light scattering techniques.

[0041] A variety of suitable colorants can be used, including suitable coloring pigments, dyes, and mixtures thereof. Examples of suitable colorants include carbon black such as REGAL® 330 carbon black, acetylene black, lamp black, aniline black, chrome yellow, zinc yellow, SICOFAST yellow, SUNBRITE® yellow, LUNA yellow, NOVAPERM® yellow, PY74 (monoazo yellow), chrome orange, BAYPLAST® orange, cadmium red, LITHOL® scarlet, HOSTAPERM red, PR122 (quinacridone red or pigment red 122), PR269 (naphthol red), FANAL® pink, HOSTAPERM® pink, LUPRETON pink, LITHOL red, RHODAMINE Lake B, Brilliant Carmine, HELIOGEN® blue, HOSTAPERM® blue, NEOPAN® blue, PV Examples include Fast® Blue, copper phthalocyanine, CINQUASSI® Green, HOSTAPERM® Green, titanium dioxide, cobalt, nickel, iron powder, SICOPUR 4068 FF, and iron oxides such as MAPICO® Black (Columbia), NP608 and NP604 (Northern Pigment), BAYFERROX® 8610 (Bayer), M08699 (Mobay), TMB-100 (Magnox), and mixtures thereof.

[0042] In embodiments, optional colorants exist, selected from cyan, magenta, yellow, black, or combinations thereof. Carbon black can be used with one or more other colorants, such as a cyan colorant, to produce a desired hue. In embodiments, optional colorants exist, including a combination of cyan pigment and carbon black. In further embodiments, optional colorants exist, including a combination of carbon black, copper phthalocyanine, magenta, and yellow, where in embodiments, magenta is pigment red and yellow is pigment yellow.

[0043] Colorants may be included in any preferred or desired amount. In embodiments, colorants, such as carbon black, cyan, magenta, and / or yellow colorants, are incorporated in amounts sufficient to impart the desired color to the toner. Generally, pigments or dyes are used in amounts of about 2 to 35 weight percent of the toner particles on a solids basis, for example, about 2 to 25 weight percent, or about 2 to 20 weight percent of the toner particles. In certain embodiments, the colorants are included in an amount of about 3 to 10 weight percent of the total colorants based on the total weight of the toner particles, and the total colorants include a combination of black and cyan colorants, in embodiments, carbon black and cyan. In embodiments, the colorants include a combination of carbon black and cyan, with carbon black included in an amount of about 1 to 25, or about 4 to 10, or about 5 to 7 percent of carbon black, and cyan included in an amount of about 0 to 3, or about 0.5 to 2 percent of cyan.

[0044] To incorporate a colorant into the toner, the colorant may optionally be in the form of an aqueous emulsion or aqueous dispersion of the colorant, using a surfactant such as an anionic or nonionic surfactant, and the colorant is, in embodiments, a pigment having a particle size of about 50 nanometers (nm) to about 3,000 nm, or about 100 nm to about 2,000 nm, or about 50 nm to about 1,000 nm. The pigment particle size is given as the volume-average median particle diameter measured using a Nanotrac particle size analyzer.

[0045] Anionic surfactants include sodium dodecylsulfate (SDS), sodium dodecylbenzenesulfonate, sodium dodecylnaphthalene sulfate, dialkylbenzenealkyl sulfates and sulfonates, abietic acid, and anionic surfactants of the NEOGEN® brand. Examples of preferred anionic surfactants include NEOGEN® RK, available from Daiichi Kogyo Seiyaku Co. Ltd., or TAYCA POWER BN2060 from Tayca Corporation (Japan), which is primarily composed of branched sodium dodecylbenzenesulfonate. The effective concentration of commonly used anionic surfactants is, for example, about 0.01 to about 10 weight percent, or about 0.1 to about 5 weight percent, based on the weight of the dispersion.

[0046] Examples of cationic surfactants include dialkylbenzenealkylammonium chloride, lauryltrimethylammonium chloride, alkylbenzylmethylammonium chloride, alkylbenzyldimethylammonium bromide, benzalkonium chloride, ethylpyridinium bromide, C12, C15, C17 trimethylammonium bromide, quaternary polyoxyethylalkylamine halide salts, and dodecylbenzyltriethylammonium chloride. Examples include MIRAPOL® and ALKAQUAT® available from Alkaril Chemical Company, and SANISOL® (benzalkonium chloride) available from Kao Chemicals. A preferred example of a cationic surfactant is SANISOL® B-50 available from Kao Corp., which mainly consists of benzyldimethylalkonium chloride. The effective concentration of commonly used cationic surfactants is, for example, about 0.01 to about 10 weight percent, or about 0.1 to about 5 weight percent, based on the weight of the dispersion.

[0047] Examples of nonionic surfactants include polyvinyl alcohol, polyacrylic acid, metalose, methylcellulose, ethylcellulose, propylcellulose, hydroxyethylcellulose, carboxymethylcellulose, polyoxyethylene cetyl ether, polyoxyethylene lauryl ether, polyoxyethylene octyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene oleyl ether, polyoxyethylene sorbitan monolaurate, polyoxyethylene stearyl ether, polyoxyethylene nonylphenyl ether, and dialkylphenoxypoly(ethyleneoxy)ethanol, which are available from Rhone-Poulenc Inc. as IGEPAL® CA-210, IGEPAL® CA-520, IGEPAL® CA-720, IGEPAL® CO-890, IGEPAL® CO-720, IGEPAL® CO-290, IGEPAL® CA-210, ANTAROX® 890, and ANTAROX® 897. A suitable example of a nonionic surfactant is ANTAROX® 897, available from Rhone-Poulenc Inc., which mainly consists of alkylphenol ethoxylates. The effective concentration of commonly used nonionic surfactants is, for example, about 0.01 to about 10 weight percent, or about 0.1 to about 5 weight percent, based on the weight of the dispersion.

[0048] In addition to polymer binders (styrene-acrylate resins) and colorants, the toner may further contain wax, in embodiments used in the form of a wax dispersion, to form the toner. The wax, when included in the toner formulation, can help improve the toner's offset resistance, for example, in low-oil or oil-free fixing designs, by helping to release the toner from the fixing roll.

[0049] Examples of waxes that can be selected include polyolefins such as polymethylene, polyethylene, polypropylene, and polybutene, as well as waxes produced by the Fischer-Tropsch process. In embodiments, the toner includes a wax selected from members of the group consisting of Fischer-Tropsch wax, polyethylene wax, paraffin wax, and combinations thereof. In embodiments, the wax is Fischer-Tropsch wax. In other embodiments, the wax is paraffin wax. In yet another embodiment, the wax is polyethylene wax. In yet another embodiment, the wax includes a combination of paraffin wax and one or more Fischer-Tropsch waxes.

[0050] In embodiments, the wax is a linear Fischer-Tropsch wax derived from carbon monoxide or other low molecular weight feedstock, such as those produced by Sasol or Shell-Malaysia. The wax may have a peak melting temperature of about 70°C to about 100°C, or about 85°C to about 95°C, as measured using differential scanning calorimetry.

[0051] In this embodiment, the wax is a linear hydrocarbon having about 46 to about 56 carbon atoms and a peak melting temperature of about 88°C to about 100°C.

[0052] In this embodiment, the wax is a polyethylene wax having a peak melting temperature of approximately 85°C to approximately 110°C, or approximately 95°C to approximately 105°C.

[0053] Any suitable or desired paraffin wax can be selected for the embodiments herein. In the embodiments, the paraffin wax may be BW-422 and BW-436 (Blended Waxes, Inc.); IGI 1245A, IGI 1250A, IGI 1297A, IGI 1266A (all manufactured by the International Group, Inc.); Indrawax 6062-F, Indrawax 6264-F, Indrawax 6466-F, Indrawax 6668-F, Indrawax 6870-F, Indrawax 7072-F, Indrawax 8070, Indrawax 6062-S 140-144, Indrawax 6062-S (all manufactured by Industrial Raw Materials LLC); Shell Sarawax SX70 (Alpha The following can be selected: paraffin waxes (made of wax); Strahl & Pitsch 434 and 674 paraffin waxes; paraffin wax dispersions (all manufactured by BYK Additives & Instruments) including CHEMBEAD® 30, CHEMBEAD® 30-AM, PARAFINE 30, PARAFFIN 60, PARAFFIN EMULSION 135-45 FDA, and PARAFFIN EMULSION 150-45 FDA; and combinations thereof.

[0054] To incorporate wax into toner, the wax may be in the form of an aqueous emulsion or an aqueous dispersion of solid wax, and the particle size of the solid wax is typically in the range of about 100 to 500 nm. Particle size refers to the volume-average median particle diameter measured using a Nanotrac particle size analyzer employing dynamic light scattering technology.

[0055] In the embodiment, the toner contains a total amount of wax of about 3.5 to about 20 weight percent, or about 5 to about 20 weight percent, or about 7 to about 20 weight percent, or about 9 to about 16 weight percent, based on the weight of the toner.

[0056] The toners of this specification may also contain flocculants or coagulants such as monovalent metal coagulants, divalent metal coagulants, and polyionic coagulants. Various coagulants are known in the art. As used herein, “polyionic coagulant” refers to a coagulant that is a salt or oxide such as a metal salt or metal oxide formed from a metal species having a valency of at least 3, preferably at least 4 or 5. Accordingly, suitable coagulants include, for example, aluminum-based coagulants such as polyaluminum fluoride and polyaluminum chloride (PAC), polyaluminum silicates such as polyaluminum sulfosilicate (PASS), polyaluminum hydroxide, and polyaluminum phosphate. Other suitable coagulants include, but are not limited to, tetraalkylthitinates, dialkyltin oxides, tetraalkyltin hydroxides, dialkyltin hydroxides, aluminum alkoxides, alkylzincs, dialkylzincs, zinc oxide, tin oxide, dibutyltin oxide, dibutyltin hydroxide, tetraalkyltin, and combinations thereof. When the coagulant is a polyionic coagulant, the coagulant may have any desired number of polyionic atoms present. For example, in embodiments, a suitable polyaluminum compound may contain about 2 to about 13, or about 3 to about 8, aluminum ions in the compound. In embodiments, a polyaluminum chloride coagulant is selected.

[0057] Such coagulants can be incorporated into toner particles during particle aggregation. Thus, the coagulant can be present in the toner particles in an amount of about 0 to about 5 weight percent, or about 0 to about 3 weight percent, on a dry weight basis, excluding external additives. In embodiments, the coagulant (or coagulant) is used in an amount of about 0.18 pph based on the total weight of the toner.

[0058] For high gloss, the presence of aluminum metal and / or metal ions in the final toner particles is undesirable because aluminum inhibits the gloss that can be obtained (the higher the aluminum content, the lower the gloss of the toner, for example due to crosslinking). Therefore, aluminum needs to be substantially extracted from the formed toner particles. Such extraction can be carried out by any preferred method, but the method in the embodiment involves adding a chelating agent or sequestering agent to the aggregated toner particles to extract aluminum ions therefrom in a controlled manner, i.e., in a manner that the final aluminum content present in the toner can be controlled. In the embodiment, ethylenediaminetetraacetic acid (EDTA), commercially available as VERSENE® 100, sodium silicate solution, etc., may be selected as the sequestering agent or chelating agent.

[0059] A chelating agent or sequestering agent may be added in an amount effective to extract aluminum ions from the solution such that the final aluminum content in the toner is less than about 1,000 ppm, based on the total weight of the toner, for example, about 1 ppm to about 1,000 ppm, or about 350 ppm to about 550 ppm, or about 425 ppm to about 475 ppm, where ppm is parts per million. The amount of chelating agent or sequestering agent added may be about 0.01 to about 10 weight percent of the solution, and the solution may contain 39 weight percent, or about 0.01 to about 5 percent, or about 0.5 to about 5 percent of the active chelating agent, based on the total weight of the toner. In embodiments, the chelating agent, in embodiments, EDTA, is selected in an amount of about 0.79 pph, based on the total weight of the dry toner particles, where pph is a percentage.

[0060] In the embodiment, the chelating agent or sequestering agent is substantially absent in the final toner and is therefore added in an amount substantially equal to the amount necessary to achieve the aforementioned amount of aluminum in the final toner, and not substantially exceeding such an amount so as not to retain an excess of the sequestering agent or chelating agent in the toner.

[0061] Chelating agents or sequestering agents may be added near the end of the agglomeration step in the emulsion agglomeration toner particle formation process, but such extraction may also be performed at any time following agglomeration and before any coalescence step.

[0062] Optionally, the toner particles may contain other optional additives. For example, the toner may contain a positive or negative charge regulator in any desired or effective amount, in embodiments at least about 0.1 weight percent of the toner, or at least about 1 weight percent of the toner, or about 10 weight percent or less of the toner, or about 3 weight percent or less of the toner. Examples of suitable charge regulators include, but are not limited to, alkylpyridinium halides, bisulfates, quaternary ammonium compounds such as alkylpyridinium compounds, including those disclosed in U.S. Patent No. 4,298,672 which is incorporated entirely herein by reference, organic sulfate and sulfonate compositions, including those disclosed in U.S. Patent No. 4,338,390 which is incorporated entirely herein by reference, cetylpyridinium tetrafluoroborate, distearyldimethylammonium methyl sulfate, aluminum salts such as BONTRON E84 (trademark) or E88 (trademark) (Hodogaya Chemical), and mixtures thereof. Such charge control agents may be applied simultaneously with the shell resin or after the shell resin has been applied.

[0063] When preparing toner by emulsion agglutination, one or more surfactants may be used during the process. Suitable surfactants include the anionic, cationic, and nonionic surfactants mentioned above.

[0064] Any suitable emulsion agglutination procedure may be used to form emulsion agglutinated toner particles. These procedures typically include basic process steps of at least agglutinating an aqueous latex emulsion containing a binder polymer, a colorant, a wax, optionally one or more surfactants, a coagulant, and any additional optionally selected additives to form aggregates, optionally adding latex shell material to form a shell on the agglutinated core particles, optionally extracting metal (aluminum) from the particles, subsequently optionally combining or fusing the aggregates, and then recovering the resulting emulsion agglutinated toner particles, optionally washing them, and optionally drying them.

[0065] In one embodiment, a method for preparing a toner containing emulsion-aggregated core-shell toner particles comprises: obtaining a core styrene-acrylate copolymer latex, an aqueous dispersion of an optional colorant, and an aqueous dispersion of wax; forming a mixture of the core styrene-acrylate copolymer latex, an aqueous dispersion of an optional colorant, and an aqueous dispersion of wax; heating the mixture to a first temperature; maintaining the first temperature to form aggregated toner particles; adding the shell styrene-acrylate copolymer latex to form a shell on the aggregated particles; optionally adding a chelating agent solution; stopping further aggregation and raising the temperature to a second temperature higher than the first temperature to coalesce the aggregated particles; and subsequently cooling, optionally washing, and recovering the emulsion-aggregated toner particles.

[0066] In certain embodiments, the toner according to this specification comprises emulsion aggregated toner particles including a core and a shell thereon, wherein the core comprises a combination of at least two styrene-acrylate copolymers selected from a first core styrene-acrylate copolymer, a second styrene-acrylate copolymer, and a third styrene-acrylate copolymer, a wax, and an optional colorant, the first core styrene-acrylate copolymer The styrene-acrylate copolymer has a weight-average molecular weight of approximately 32,000 g / mol to approximately 38,000 g / mol and an onset glass transition temperature of approximately 57.0°C to approximately 61.0°C, the second core styrene-acrylate copolymer has a weight-average molecular weight of approximately 52,000 g / mol to approximately 58,000 g / mol and an onset glass transition temperature of approximately 53.0°C to approximately 57.0°C, and the third core styrene-acrylate copolymer has a weight-average molecular weight of approximately 33,000 g / mol to approximately 39,000 g / mol The shell has an average molecular weight and an initial glass transition temperature of approximately 49.0°C to approximately 53.0°C, and comprises at least one styrene-acrylate copolymer selected from a first shell styrene-acrylate copolymer, a second shell styrene-acrylate copolymer, or a combination thereof, wherein the first shell styrene-acrylate copolymer has a weight-average molecular weight of approximately 32,000 g / mol to approximately 38,000 g / mol and an initial glass transition temperature of approximately 57.0°C to approximately 61.0°C. The toner comprises emulsion-aggregated toner particles having a glass transition temperature, and the second shell styrene-acrylate copolymer having a weight-average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an initial glass transition temperature of about 53.0°C to about 57.0°C, wherein the toner contains, based on the total weight of the toner, about 50 to about 60 weight percent core, about 26 to about 30 weight percent shell, about 3 to about 10 weight percent colorant, and about 7 to about 20 weight percent wax.

[0067] In the embodiment, the toner particles have a volume-average median particle diameter of about 1 to about 15 micrometers, or about 2 to about 10 micrometers, or about 4 to about 9 micrometers, as measured using a Coulter Counter Multisizer 3. In the embodiment, the toner particles have an average circularity of about 0.93 to about 0.98, as measured using a Malvern Sysmex Flow Particle Image Analyzer (FPIA3000). Circularity is a measure of how close a particle is to a perfect sphere. A circularity of 1.0 identifies particles that have the shape of a perfect sphere.

[0068] The cohesiveness of toner particles is, to some extent, related to the surface morphology of the particles. If the particle surface is rounder / smoother, the cohesive force will be lower and the fluidity will be higher. If the surface is less rounded / rougher, the fluidity will be worse and the cohesive force will be higher.

[0069] Toner particles may also have a diameter distribution such that the volume geometric standard deviation (GSDv) of (D84 / D50) is in the range of approximately 1.15 to approximately 1.25. The volume-average particle diameter at which a cumulative percentage of 50% of the total toner particles is achieved is defined as volume D50, and the volume-average particle diameter at which a cumulative percentage of 84% is achieved is defined as volume D84. These above volume-average particle diameter distribution indices GSDv can be expressed by using D50 and D84 in the cumulative distribution, and the volume-average particle diameter distribution indices GSDv are expressed as (volume D84 / volume D50). The GSDv value of toner particles indicates that the toner particles are manufactured to have a very narrow particle diameter distribution.

[0070] Furthermore, external additive particles containing flow-enhancing additives can be blended with the toner particles, which may be present on the surface of the toner particles. Examples of these additives include, but are not limited to, metal oxides such as titanium dioxide, silicon dioxide, and tin oxide, as well as mixtures thereof; colloidal and amorphous silica such as AEROSIL®, metal salts; and metal salts of fatty acids including zinc stearate, aluminum oxide, and cerium oxide, as well as mixtures thereof. Each of these external additives may be present in any desired or effective amount, in embodiments, at least about 0.1 weight percent of the toner, or at least about 0.25 weight percent of the toner, or about 5 weight percent or less of the toner, or about 3 weight percent or less of the toner. Suitable additives include, but are not limited to, those disclosed in U.S. Patent Nos. 3,590,000 and 6,214,507, each of which is incorporated herein by reference. Such additives may be applied simultaneously with the shell resin or after the application of the shell resin.

[0071] The toner of the present invention may be incorporated into a developer composition. The developer composition can be prepared by mixing the toner of this disclosure with known carrier particles, including coated carriers such as steel and ferrite. Examples of such carriers are disclosed in U.S. Patents No. 4,937,166 and No. 4,935,326, the entirety of each of these disclosures being incorporated herein by reference.

[0072] The toner may be present in the carrier in amounts of approximately 1% to 15% by weight, approximately 2% to 8% by weight, or approximately 4% to 6% by weight. The carrier particles may also include a core having a polymer coating such as polymethyl methacrylate (PMMA), in which a conductive component such as conductive carbon black is dispersed. Examples of carrier coatings include silicone resins such as methylsilsesquioxane, fluoropolymers such as polyvinylidene fluoride, mixtures of resins that are not adjacent in the triboelectric series, such as polyvinylidene fluoride and acrylic, thermosetting resins such as acrylic, combinations thereof, and other known components.

[0073] The toner of the present invention can be used in various electrophotographic processes with various electrophotographic printers. An electrophotographic imaging process includes, for example, preparing an image in an electrophotographic printer comprising a charging component, an imaging component, a photoconductive component, a developing component, a transfer component, and a fixing component. In embodiments, the developing component may include a developer prepared by mixing a carrier with any of the toners described herein. The electrophotographic printer may include high-speed printers, black-and-white high-speed printers, color printers, and the like. Once an image is formed with the toner / developer, the image can then be transferred to an image-receiving medium such as paper. A fuser roll member may be used to fix the toner to the image-receiving medium by using heat and pressure. By using the toner of the present invention in an electrophotographic printing process, printed images having the properties described herein and other desirable properties can be provided.

[0074] The toners of this invention are found to be used in other applications such as powder coating applications in which a powder spray gun (e.g., a tribogun) containing any of the toners of this invention is used to supply the toner to a substrate.

[0075] In embodiments, the process described herein includes forming an image with the toner described herein using an electrophotographic printer, transferring the toner-containing image to an image receiving medium, and fixing the toner to the image receiving medium to form a toner image. [Examples]

[0076] The following embodiments are provided to further define the various types of this disclosure. These embodiments are for illustrative purposes only and are not intended to limit the scope of this disclosure. Unless otherwise stated, proportions and percentages are given by weight.

[0077] The toner was prepared using the following aggregation / combination process.

[0078] 1. The core materials (latex, pigment, wax) and deionized water were mixed in a gallon reactor.

[0079] 2. The contents of the reactor were homogenized using a rotor / stator homogenizer, and a polyaluminum chloride flocculant was added.

[0080] 3. The reactor was heated to 52°C to 59°C for coagulation. The stirring speed was set according to the slurry viscosity. Particle size (D50v) was monitored using a Coulter Multisizer-3 measuring instrument.

[0081] 4. Once a pre-shell particle size of approximately 5.3 micrometers was achieved, the shell latex was added to the reactor using a metering pump.

[0082] 5. The pH of the slurry was increased to 4.5-5.7 by adding NaOH solution and Versene® 100 solution. The stirring speed was gradually reduced according to the viscosity. The batch was then held for 10 minutes.

[0083] 6. The reactor was heated to approximately 80°C. HNO3 solution was added to the reactor to achieve a pH of 4.0–5.2. The reactor was then heated to a mating temperature of 92.0–98.0°C.

[0084] The reactor was maintained at the maturation temperature until a circularity of 7.0.970 to 0.975 was achieved. Circularity was monitored using an FPIA Sysmex 3000 instrument.

[0085] 8. Next, NaOH solution was added to raise the pH to 6.0. Then, the reactor was cooled to below 63°C, and the pH was further increased to 8.8 using 1M NaOH. Then, the reactor was cooled to room temperature.

[0086] 9. The contents of the reactor were collected, then sieved, washed, and dried using conventional methods.

[0087] The material properties table is as follows. In Table 2, as described herein, Sty-A1 means styrene-acrylate copolymer 1, Sty-A2 means styrene-acrylate copolymer 2, and Sty-A3 means styrene-acrylate copolymer 3. [Table 1] [Table 2] [Table 3]

[0088] The properties of the toner can be fine-tuned by changing the type and amount of raw materials used in the agglomeration / combination process. The overall toner molecular weight (Mw) and glass transition temperature (Tg) may be influenced by the core latex and shell latex. The examples show various combinations of three styrene-acrylic latexes, each having its own Tg and Mw. The toner compositions were directed toward increasing Tg and Mw to improve the storage stability and durability of the toner. Different latex compositions selected for the particle core and particle shell are chosen to further optimize the toner properties. Higher Tg and Mw in the shell are generally preferred to improve storage stability and durability, while lower Tg and Mw in the core are generally preferred to improve gloss and low melting properties.

[0089] Wax formulations can significantly affect toner melting properties. Low-melting waxes, such as paraffin, result in increased melt flow (lower T1 / 2) and decreased Tg. Wax can also affect other mechanical performance metrics, such as hot offset and ultrafine particle emission. In embodiments, the type and amount of wax are selected to influence these properties.

[0090] Aluminum complexes used as flocculants can also affect toner melting properties. Residual aluminum can crosslink the bonded resin, leading to a decrease in melt flow. This can result in reduced floss and fixation properties. While a minimum amount of flocculant is desired to promote flocculation, chelating agents can be added during the freezing process to remove excess aluminum.

[0091] In the embodiment, two levels of pigment filling were selected to observe the dielectric loss and optical density range due to carbon black.

[0092] Particle size and shape affect many electrophotographic properties, such as tribolysis, fluidity, and transferability. This toner composition allows for a wide range of toner sizes and shapes to meet mechanical requirements and provide the desired toner properties. [Table 4]

[0093] A toner particle composition containing the following components was prepared. Examples 9 to 22, having the components shown in Table 5 below, were prepared by the process described above. [Table 5]

[0094] The characteristics of Examples 9 to 22 are shown in Tables 6 and 7. [Table 6] [Table 7]

[0095] It will be understood that various features and functions disclosed above, or alternatives thereof, may be desirablely combined in many other different systems or applications. Furthermore, various currently unforeseen or unprecedented alternatives, modifications, variations, or improvements may be made by those skilled in the art, and these are also intended to be covered by the following "Claims." Unless specifically enumerated in the Claims, no process or component of the Claims should be implied or understood in any particular order, number, position, size, shape, angle, color, or material from this Specified or any other Claims.

Claims

1. A toner comprising toner particles comprising a core and a shell thereon, the core comprises a first core styrene-acrylate copolymer and a second core styrene-acrylate copolymer, a wax, and an optional colorant; the first core styrene-acrylate copolymer is a styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an onset glass transition temperature of about 57.0° C. to about 61.0° C.; the second core styrene-acrylate copolymer is a styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an onset glass transition temperature of about 53.0° C. to about 57.0° C.; the shell comprises a single styrene-acrylate copolymer; the single shell styrene-acrylate copolymer is a first styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an onset glass transition temperature of about 57.0°C to about 61.0°C.

2. The toner comprises, based on a total weight of the toner, about 50 to about 80 weight percent of a core; about 20 to about 36 weight percent of a shell; about 3 to about 10 weight percent colorant; 10. The toner of claim 1 comprising from about 5 to about 20 percent by weight of the wax.

3. A toner comprising toner particles including a core and a shell thereover, the core comprising a combination of a first core styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol, and an onset glass transition temperature of about 57.0°C to about 61.0°C, and a second core styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 52,000 g / mol to about 58,000 g / mol, and an onset glass transition temperature of about 53.0°C to about 57.0°C.

4. 2. The toner of claim 1, wherein said wax is selected from a member of the group consisting of polyethylene waxes, paraffin waxes, Fischer-Tropsch waxes, and combinations thereof.

5. 2. The toner of claim 1, wherein said wax is a Fischer-Tropsch wax having a peak melting temperature of from about 70°C to about 100°C.

6. 2. The toner of claim 1, wherein the wax is a paraffin wax.

7. 2. The toner of claim 1, wherein the wax is a polyethylene wax.

8. 10. The toner of claim 1, wherein said optional colorant is present and said colorant is selected from cyan, magenta, yellow, black, or combinations thereof.

9. The toner of claim 1 , wherein said optional colorant is present and said colorant comprises a combination of a cyan pigment and carbon black.

10. The toner of claim 1 further comprising a coagulant, a chelating agent, or a combination thereof.

11. The toner of claim 1, having an onset glass transition temperature (Tg) of about 53.0° C. to about 60.0° C.

12. 1. A method of preparing a toner, including emulsion aggregation core-shell toner particles, comprising: the core comprises a first styrene-acrylate copolymer, a second styrene-acrylate copolymer, a wax, and an optional colorant; the first styrene-acrylate copolymer is a styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an onset glass transition temperature of about 57.0° C. to about 61.0° C.; the second styrene-acrylate copolymer is a styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 52,000 g / mol to about 58,000 g / mol and an onset glass transition temperature of about 53.0° C. to about 57.0° C.; The method further comprising: obtaining a latex of said core styrene-acrylate copolymer, an aqueous dispersion of said optional colorant, and an aqueous dispersion of said wax; forming a mixture of the latex of the core styrene-acrylate copolymer, the aqueous dispersion of the optional colorant, and the aqueous dispersion of the wax; heating the mixture to a first temperature; maintaining said first temperature to form aggregate toner particles; adding a latex of a shell styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer to form a shell on the agglomerated particles; Optionally, adding a solution of a chelating agent; stopping further aggregation and increasing the temperature to a second temperature greater than the first temperature to coalesce the aggregated particles. followed by cooling and optionally washing and recovering the emulsion aggregation toner particles.

13. The method of claim 12, wherein the toner shell comprises a single styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer, the single shell styrene-acrylate copolymer being the first styrene-n-butyl acrylate-β-carboxyethyl acrylate copolymer having a weight average molecular weight of about 32,000 g / mol to about 38,000 g / mol and an onset glass transition temperature of about 57.0°C to about 61.0°C.

14. the wax is selected from the group consisting of Fischer-Tropsch waxes, polyethylene waxes, paraffin waxes, and combinations thereof; 13. The method of claim 12, wherein the optional colorant is present and is selected from cyan, magenta, yellow, black, carbon black, copper phthalocyanine, PR122, PR269, PY74, or combinations thereof.

15. The method of claim 12, comprising a batch emulsion aggregation process.

16. The method of claim 12, wherein the toner has an onset glass transition temperature (Tg) of from about 53.0° C. to about 60.0° C.